The Effect of the Problem Posing Learning Model on the Critical Thinking Skills of Fifth Grade Students in Mathematics - Fitriani, Dela; Hidayah, Nurul; Afriyadi, Muhammad Muchsin (STKIP Al Islam Tunas Bangsa dan HEPI, 2025)
The learning process applied by educators has varied in the use of learning models; however, students' critical thinking skills are still considered low. In light of this issue, the researcher attempted to implement a learning process using a model that had never been used by educators before, namely the problem posing learning model. This study aims to examine the effect of the problem posing learning model on the critical thinking skills of fifth-grade students in mathematics at MIN 10 Bandar Lampung. The research employed a quantitative approach with a quasi-experimental design (post-test only control group design). The study was conducted at MIN 10 Bandar Lampung, specifically in the fifth grade, involving two classes as the experimental and control groups, as well as an additional class for validation purposes. The instruments used in this study included tests. Data analysis was performed using the t-test. The results showed that the normality test yielded values of 0.180 and 0.054, both greater than 0.05, indicating that the data were normally distributed. The homogeneity test showed a value of 0.918, which is also greater than 0.05, indicating that the data were homogeneous. The hypothesis test using the Independent Samples t-Test resulted in a value of 0.000, which is less than 0.05, meaning that the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. Therefore, it can be concluded that there is a significant effect of the problem posing learning model on the critical thinking skills of fifth-grade mathematics students at MIN 10 Bandar Lampung.